Perceptions of health care workers regarding the participation of men in HIV programmes - Dhlamini, Zandile Faith (My University, 2008)
This study explores the perceptions of health care workers regarding men’s participation in HIV programmes with the objective of identifying factors that may facilitate or hinder the participation of men in such programmes. A sub aim was to explore how perceptions regarding the effects of different constructions of masculinity may be implicated in the ways men respond to HIV programmes. The study was conducted with permission from HIV/AIDS clinics: Thembalethu clinic in the Helen Joseph Hospital, Tshwarisanang couples’ VCT clinic at Chris Hani Baragwanath hospital and two Johannesburg University campus clinics. Data was collected using a purposive sample of 8 health care workers. Each participant took part in one-on-one semi-structured interviews, which yielded the results of this study. The data was analysed using thematic content analysis. The results showed that a majority of the health care workers perceived men to be nonparticipatory in HIV programmes. They perceived barriers to men’s participation to be men’s varied perception of fear knowing their HIV status, fear of dying and fear of the emotional consequences of testing positive such as anger and depression. Men also see counselling as a sign of weakness and as a result, they do not participate in HIV programmes. In conclusion, health care workers identified the need to develop new strategies and best suited programmes that promote HIV testing amongst men.
Keywords: participation; health care workers; men; masculinity; HIV programmes